1996
DOI: 10.1021/ma960428b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Inclusion Complexes of Polyisobutylene with Cyclodextrins

Abstract: β-Cyclodextrin (β-CD) and γ-cyclodextrin (γ-CD) formed inclusion complexes with polyisobutylene (PIB) of various molecular weights to give stoichiometric compounds in crystalline states. R-Cyclodextrin (R-CD) did not form complexes with PIB of any molecular weight. The yields of the complexes with β-CD decreased with an increase in the molecular weight of PIB. In contrast, the yields of the complexes with γ-CD increased with an increase in the molecular weight and the complexes were obtained almost quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
176
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 149 publications
(196 citation statements)
references
References 18 publications
19
176
1
Order By: Relevance
“…[13] We also found that CDs form complexes not only with hydrophilic polymers, but also with hydrophobic polymers having low molecular weights, such as polyethylene (PE), [14] polypropylene (PP) and polyisobutylene (PIB). [15] β-CD formed complexes with PP and PIB, but not with PE. Again, there is a good correlation between the sizes of CDs and the cross-sectional area of the above polymers.…”
Section: Formation Of Inclusion Complexes Of Cds With Polymersmentioning
confidence: 87%
“…[13] We also found that CDs form complexes not only with hydrophilic polymers, but also with hydrophobic polymers having low molecular weights, such as polyethylene (PE), [14] polypropylene (PP) and polyisobutylene (PIB). [15] β-CD formed complexes with PP and PIB, but not with PE. Again, there is a good correlation between the sizes of CDs and the cross-sectional area of the above polymers.…”
Section: Formation Of Inclusion Complexes Of Cds With Polymersmentioning
confidence: 87%
“…Similarly, signals representing for C 3 and C 5 were integrated into peak at 72.6 ppm in the complexed a-CD. Peaks integration indicated that the a-CD adopted the symmetrical conformation in the crystalline inclusion complexes (Harada, Suzuki, Okada, & Kamachi, 1996;Li, Mai, Yan, & Chen, 2003;Lu et al, 2000). The chemical shift for C3 and C5 characterise for the inclusion of guest molecule into the cavity of complexed CD (Astakhova & Demina, 2004).…”
Section: Nmr Spectroscopymentioning
confidence: 97%
“…The opposite ICD signals observed between 1 and 2 indicate that not only do the DPD molecules still lie in the cavity of bCDs after the formation of 2, but also that the DPD moiety of 2 may become more acclivitous in the cavity of b-CDs after coordination of Ni II ions. The powder X-ray diffraction patterns [8,23] of b-CD, DPD, 1, and 2 were obtained using a Rigaku D/max-2500 diffractometer with CuKa radiation. The diffractogram of b-CDs shows a characteristic reflection at 2q = 12.48(d = 7.…”
Section: à041 Dmmentioning
confidence: 99%